Dampak Sosial Ekonomi Pariwisata di Pulau Saronde oleh PT. Blue Bay Divers - Rivaldi Unti; Rauf A. Hatu; Dewinta Rizky R. Hatu (Program Studi Sosiologi, Fakultas Ilmu Sosial Universitas Negeri Gorontalo, 2026)
This study aims to analyze the socio-economic impacts of tourism on Saronde Island after its management was taken over by PT. Blue Bay Divers, focusing on the community of Ponelo Village, North Gorontalo Regency. The research is based on the decreasing participation of local residents in tourism activities following privatization. The study employs a qualitative descriptive method using field studies through observation, interviews, and documentation. The findings reveal that the presence of PT. Blue Bay Divers has significantly affected the social and economic dynamics of the local community. Economically, local workforce involvement decreased by up to 90%, and only two small businesses remain from the original fifteen. Socially, there has been a decline in social cohesion and a widening gap between groups involved in tourism and those excluded. The community has lost access and participation opportunities, resulting in social alienation and new economic dependency on tourism. The study concludes that the development of tourism on Saronde Island remains exclusive and has not provided equitable benefits to local residents. Inclusive policies and human resource empowerment are needed to ensure that tourism becomes a vehicle for social solidarity and economic independence in Ponelo Village.